Analysis of Relationship Between Dividend Policy and Financial Performance in Deposit Money Banks in Nigeria - Abalaka, J.N; Ajiteru,S.A.R; Sulaiman T.H (International Forum of Researchers and Lecturers, 2025)
This study set out to investigate the connection between Nigerian deposit money banks' financial success and their dividend policies. This is accomplished by reviewing existing theoretical and empirical the signaling hypothesis served as the foundation for the study and the creation of literature. The Financial Statements and Annual Reports of 18 (18) Deposit Money Banks in Nigeria for the years 2015–2019 provided the data for this study, which used a longitudinal survey research approach. The arithmetic mean, standard deviation, minimum and maximum values, and the Auto-Regressive Distributed Lag (ARDL) regression technique were used to analyze the data produced for this study using both descriptive and inferential statistics. E-Views version 10 was used to calculate these. The study's conclusions showed that dividend policies had a mixed impact on the financial performance of Nigerian deposit money institutions. However, the dividend pay-out ratio significantly and negatively correlates with financial performance (return on equity), dividend yield has no discernible impact on the financial performance (ROE) of Nigerian deposit money institutions. The greatest African economy is that of Nigeria, which was rated as Determining the percentage of dividend payments that would improve financial performance in terms of return on equity requires management of deposit money banks to have a strong and sound dividend policy in place. They should also put in more effort to raise dividend yield and improve its influence on the financial performance (return on equity) of deposit money banks in Nigeria.